Modernization and the Logic of Interorganizational Networks - Renate Mayntz (Max-Planck-Institut für Gesellschaftsforschung; Max-Planck-Gesellschaft zur Förderung der Wissenschaften e.V., 1991)
In recent years, scholars in a variety of disciplines have become interested in why there is variation in the institutional arrangements for coordination and control of economic activities in capitalist economies. Some have attempted to explain why transactions occur among actors within a market, a firm, or some form of network. Another body of scholarship has attempted to understand why there are collective forms of behavior among economic actors. This paper attempts to integrate these two traditions by developing a typology of two forms of coordination and control: coordination for coping with transactions . among various actors and. forms of coordinating collective behavior. Focusing on the economy- of the United States since the late nineteenth century, this paper offers suggestions of why one form of coordination rather than another emerges, how various forms of coordination are related to one another, and how specific forms of coordination might influence the economic performance of various industries. – – In den letzten Jahren haben sich Wissenschaftler verschiedener Disziplinen für die Frage interessiert, warum sich die institutionellen Strukturen kapitalistischer Wirtschaftssysteme für die Koordination und Steuerung wirtschaftlicher Prozesse unterscheiden müssen. Einige haben zu erklaren versucht, wieso Transaktionen zwischen Akteuren in Markten, Firmen oder anderen Netzwerkformen zustande kommen. Andere haben zu verstehen versucht, wie kollektive Verhaltensformen zwischen Wirtschaftsakteuren entstehen. Das vorliegende Papier will beide Traditionen mit Hilfe einer Typologie zweier Steuerungs- und Koordinationsformen integrieren: Koordination, um mit Transaktionen zwischen verschiedenen Akteuren fertig zu werden, und Arten der Koordinierung kollektiven Verhaltens. Fokussiert auf das Wirtschaftssystem der Vereinigten Staaten seit dem späten 19. Jahrhundert, entwickelt dieses Papier Hypothesen über die Emergenz einzelner Koordinationsformen, die Beziehungen zwischen diesen und den möglichen Einfluß spezifischer Typen der Koordination auf unterschiedliche Industriezweige.
Keywords: 300